The Determinant of Socio-Demographic Factors, the Environment, and Access to Health Services on the Prevalence of Stunting Among Children Aged 6–24 Months in West Aceh Regency - Teungku Nih Farisni; Herlina Dimiati; Aman Yaman; Sri Wahyuni (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2026)
Stunting remains a major public health challenge in Indonesia, particularly in regions with persistent socio-economic disparities such as West Aceh District. This condition reflects not only chronic undernutrition during the first 1,000 days of life but also the complex interaction of social, environmental, and health system factors. Therefore, a comprehensive approach that integrates socio-demographic determinants with broader development perspectives is required. This study aimed to analyze the influence of socio-demographic factors, environmental conditions, and access to health services on stunting among children aged 6–24 months in West Aceh District, Indonesia, while interpreting the findings within the framework of the Three Domains of Pancasila: value (mental-cultural), governance (institutional-political), and welfare (material-technological).This study employed an analytical cross-sectional design involving 80 children aged 6–24 months. Data were collected through structured interviews using validated questionnaires covering socio-demographic characteristics (maternal education, occupation, and socio-economic status), environmental conditions (sanitation, clean water access, and housing density), and access to health services (distance, affordability, and family support). Child growth status was assessed using Length-for-Age Z-score (LAZ) based on WHO standards. Data were analyzed using univariate, bivariate (chi-square), and multivariate logistic regression analyses.The results showed that maternal education, socio-economic status, sanitation, and access to health services were significantly associated with stunting (p < 0.05). Multivariate analysis identified sanitation and socio-economic status as the most dominant determinants. These findings indicate that stunting is shaped by multidimensional factors that extend beyond nutritional intake alone.From the perspective of the Three Domains of Pancasila, these results highlight the importance of strengthening community awareness and cultural practices related to nutrition (value domain), improving equitable access to health services (governance domain), and enhancing living conditions and environmental health (welfare domain). Therefore, stunting prevention requires an integrated, context-specific approach that aligns public health interventions with socio-cultural values and local development systems